Mesa: um atlas da poesia portuguesa moderna e contemporânea - Constance Von Krüger de Alcântara e Silva (2023)
The work presented here aims to address the following question: would the table, this trivial object, be a formula of pathos in modern and contemporary Portuguese poetry? The hypothesis that is launched starts from the observation – in the poems that make up the corpus of the research – that this piece of furniture survives, through words, in an imagery way, and that its presence announces more than the triviality that is supposed of an everyday object, such as will be demonstrated in the chapter dedicated to its history. To deal with the question proposed about the table (and on it), we ask for the concepts of Pathosformel and Nachleben, thought by Aby Warburg, are requested, as well as the way of thinking (expressed by the work of Passages) of the also German Walter Benjamin. This principle of concepts and methods research, in theoretical terms, makes this research affiliated with a transversal, constellar, and, mainly, iconographic thinking. Although the theoretical path is the first conductor of the following text, it is from the poems that this research is born. More specifically, the reading of these poems, and the verification of the table‘s recurrence in a corpus (chosen exclusively for a necessary cut for the execution of the research, in practical terms). We claim, from the Warburgian inspiration of his atlas Mnemosyne, to present such poems on panels guided by formulas of pathos verifiable as recurrences of the table, in order to compose, thus, an atlas of the table in modern and contemporary Portuguese poetry. Finally, we intend to discuss the double power of the table, sometimes as an operative field, sometimes as – itself – a Pathosformel.